RANCANG BANGUN MONITORING KEBERADAAN ORANG DENGAN MEMANFAATKAN LAYANAN SMS DAN INTERNET SEBAGAI MEDIA TRANSFER DATA - Nurhadi, Nurhadi; Sutanto, Teguh; Taufik, Vicky M. (Jurnal JSIKA, 2013)
Parents activities reduced their attention to children. Sometimes parents do not know their children’s activity. Even they did not know where their children. So it is not uncommon today´s children often go to places that are not fitting. Even worse was the kidnapping of children. "From year to year, kidnappings continue to rise. Not only in the city, in the village also. Our data, in 2008 there were 72 cases. Years 2009 there were 102 cases. 2010 to May has reached 97 cases," said Secretary General of the National Commission for Child Protection, Arist Merdeka Sirait, told AFP on Wednesday (02/06/2010). Until now be seen from the data that showed the National Commission for Child Protection in 2010 the total occurrence of child abduction is 111 and the total in 2011 was 120, indicating that up to now the abduction of children each year continues to increase. If the total from 2008 to 2011 the abduction of children from the National Commission for Child Protection of data is 405. 405 numbers are not small. If one of the family or relatives disappear, what would we feel? And it has been perceived by 405 more families.” Keywords: Abduction, Place, Parents, Children, Activities